2019
DOI: 10.1096/fj.201802691rr
|View full text |Cite
|
Sign up to set email alerts
|

The alarmin S100A9 hampers osteoclast differentiation from human circulating precursors by reducing the expression of RANK

Abstract: The alarmin S100A8/A9 is implicated in sterile inflammation‐induced bone resorption and has been shown to increase the bone‐resorptive capacity of mature osteoclasts. Here, we investigated the effects of S100A9 on osteoclast differentiation from human CD14+ circulating precursors. Hereto, human CD14+ monocytes were isolated and differentiated toward osteoclasts with M‐CSF and receptor activator of NF‐κB (RANK) ligand (RANKL) in the presence or absence of S100A9. Tartrate‐resistant acid phosphatase staining sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Furthermore, higher fecal calprotectin levels at baseline were reported to predict treatment response to adalimumab [32]. It is known that calprotectin subunits s100A8 and A9 have an effect on osteoclasts and osteoblasts, both seem to be involved during differentiation of osteocytes: Whilst s100A8 is suggested to play a stimulating role in osteoblast differentiation, S100A9 seems to hamper differentiation of osteoclasts [33,34]. Interestingly, calprotectin serum levels were not associated with the clinical presence or activity of concomitant inflammatory bowel disease in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher fecal calprotectin levels at baseline were reported to predict treatment response to adalimumab [32]. It is known that calprotectin subunits s100A8 and A9 have an effect on osteoclasts and osteoblasts, both seem to be involved during differentiation of osteocytes: Whilst s100A8 is suggested to play a stimulating role in osteoblast differentiation, S100A9 seems to hamper differentiation of osteoclasts [33,34]. Interestingly, calprotectin serum levels were not associated with the clinical presence or activity of concomitant inflammatory bowel disease in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although RANKL and M-CSF are usually described as the critical factors that determine if osteoclast differentiation takes place, the expression of the receptor RANK is also of importance. A couple of recent publications highlight the fact that the regulation of RANK expression is an effective means to change the effectiveness of osteoclast differentiation [37][38][39]. Indeed, RANK expression on macrophages is quite low and it is therefore not surprising that RANK abundance can be a limiting factor in osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, RANK expression on macrophages is quite low and it is therefore not surprising that RANK abundance can be a limiting factor in osteoclastogenesis. For example, di Ceglie et al recently (2019) described that the endogenous DAMP and marker for sterile inflammation in rheumatoid arthritis, the alarmin S100A9, reduced M-CSF-induced RANK expression to limit osteoclastogenesis [39].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that S100A9 directly stimulates osteoclast formation from monocytes in the context of osteomyelitis in the absence of RANKL (75). However, addition of S100A9 to human monocytes strongly inhibits osteoclast differentiation (76).…”
Section: The Effect Of Alarmins On Osteoblasts and Osteoclastsmentioning
confidence: 99%